Diverticular disease of the colon in Accra, Ghana - Baako, B.N. (British Journal of Surgery, 2001)
Diverticular disease is said to be rare in Africans because ofthe high-®bre diet they consume. Septic complications arethe main presenting symptoms in Western countries andthe major cause of morbidity and mortality from thedisease1. This 3-year (1997±2000) prospective study in oneof four general surgical units in the Korle Bu TeachingHospital in Accra examined the incidence and presentation of the disease in the indigenous Ghanaian populationadherent to a high-®bre diet.